RNA-Seq as a Tool to Study the Tumor Microenvironment - Panichnantakul, Pudchalaluck; Bourgey, Mathieu; Montpetit, Alexandre; Bourque, Guillaume; Riazalhosseini, Yasser (Methods in molecular biology (Clifton, N.J.), 2016)
The transcriptome is composed of different types of RNA molecules including mRNAs, tRNAs, rRNAs, and other noncoding RNAs that are found inside a cell at a given time. Analyzing transcriptome patterns can shed light on the functional state of the cell as well as on the dynamics of cellular behavior associated with genomic and environmental changes. Likewise, transcriptome analysis has been a major help in solving biological issues and understanding the molecular basis of many diseases including human cancers. Specifically, since targeted and whole genome sequencing studies are becoming more common in identifying the driving factors of cancer, a comprehensive and high-resolution analysis of the transcriptome, as provided by RNA-Sequencing (RNA-Seq), plays a key role in investigating the functional relevance of the identified genomic aberrations. Here, we describe experimental procedures of RNA-Seq and downstream data processing and analysis, with a focus on the identification of abnormally expressed transcripts and genes.